Effects of copper and arsenic stress on the development of Norway spruce somatic embryos and their visualization with the environmental scanning electron microscope - Đorđević, Biljana; Neděla, Vilém; Tihlaříková, Eva; Trojan, Václav; Havel, Ladislav (New biotechnology, 2019)
Somatic embryogenesis is an important biotechnological technique which can be used in studies associated with environmental stress. Four embryogenic cell lines of Norway spruce were grown on media enriched with copper and arsenic in concentration ranges 50-500 μM and 10-50 μM, respectively. The effects were observed during subsequent stages of somatic embryogenesis, the characteristics evaluated being proliferation potential, average number of somatic embryos obtained per g/fresh weight, morphology of developed somatic embryos, metal uptake, and microanalysis of macro- and micronutrients uptake. Copper and arsenic at higher concentrations significantly reduced the growth of early somatic embryos. In almost all treatments, the cell line V-1-3 showed the best performance compared with the other lines tested. Environmental scanning electron microscopy was used to visualize and identify morphological abnormalities in the development of somatic embryos. Abnormalities observed were classified into several categories: meristemless somatic embryos, somatic embryos with disrupted meristem, reduced number of cotyledons, single cotyledon and fused cotyledons. With the application of a low temperature method for the environmental scanning electron microscope, samples were stabilized and whole meristems could be investigated in their native state. As far as we are aware, this is the first report of the effect of copper and arsenic during the process of somatic embryogenesis and the first to evaluate the content of macro and micronutrients uptake in Norway spruce.
Keywords: Biotechnology; Picea abies (L.) Karst.; Environmental Pollutants; Somatic embryogenesis; buněčné linie; Cell Line; Biological Transport, Active; arsen; látky znečišťující životní prostředí; fyziologický stres; Picea; mikroskopie elektronová rastrovací; Germination; měď; Copper; Arsenic; Environmental scanning electron microscope; biotechnologie; aktivní transport; klíčení; Microscopy, Electron, Scanning; smrk; Stress, Physiological